Assessing the efficiency of health-care expenditure among low- and middle- income African countries: Sfa approach - Mohammed, Hassan Adamu; Mohamed Nor, Norashidah; Mohd Noor, Zaleha; Adam, Peter (International Institute for Science, Technology & Education, 2015)
This study used stochastic frontier analysis to determine the level of efficiency of health-care expenditure using three health outputs among low- and middle-income countries in Africa, from 2002–2011. The technical efficiency result shows that; among the health outcomes estimated, life expectancy at birth recorded higher efficiency among both low and middle-income African countries, while Anti-retrieval was the least efficient outputs. The study also calculated the expenditure savings when maximum efficiency is attained, where the average was 0.21 % and 0.29% of GDP for low and middle income countries respectively. The study recommends that governments improve not only health care expenditure but also factors affecting health other than health care to reduce the burden on health-care facilities and reduce the burden of disease in the region.